Innovative Brand Awareness Strategies: Push, Pull & Pass Marketing in Indonesian Fashion - Pricilla, Chaterina; Adriani, Vanny; Utomo, Anggayuh Gesang (Journal of Communication and Public Relations, 2023)
Several Fashion manufacturer in Indonesia are delivering distinctive themes as the country's fashion industry expands quickly. With advances in quality and design, local products are now able to compete with those of foreign brands. Public Relations has grown in importance as a marketing strategy in the apparel business in recent years. The purpose of this study is to explain how Loony's public relations marketing has increased brand awareness. This research collects primary and secondary data using a descriptive qualitative research methodology. Interviews with customers and internal business sources are used to gather primary data. Books, journals, webpages, and internal company data are sources of secondary data. This approach ensures a comprehensive analysis of Loony's strategies. The results show that Loony uses the Push, Pull, and Pass methods to boost brand recognition. The Push strategy involves actively promoting the brand, the Pull strategy focuses on attracting consumers, and the Pass strategy relies on making the brand unique by giving nicknames to its customers. By integrating these techniques, Loony has effectively raised its profile in a competitive industry. Public relations have allowed the brand to interact more meaningfully with consumers, fostering loyalty and engagement. By emphasizing distinctive regional themes and values, this tactic has also helped Loony differentiate from foreign rivals. In Indonesia's rapidly changing fashion industry, this strategy highlights the significance of strategic marketing. Effective use of marketing and PR techniques will be essential for firms to build and preserve a strong market presence as the industry expands.